Avoidant/Restrictive Food Intake Disorder: A Longitudinal Study of Malnutrition and Psychopathological Risk Factors From 2 to 11 Years of Age - Lucarelli, Loredana; Sechi, Cristina; Cimino, Silvia; Chatoor, Irene (Frontiers in Psychology, 2018)
Objective: To evaluate different types and degrees of malnutrition over time in a sample of children diagnosed with Infantile Anorexia (IA), based on the DC:0-3R criteria, and recently defined by DSM-5 as the first subtype of Avoidant/Restrictive Food Intake Disorder (ARFID), and to investigate the relationship between children’s severity of malnutrition and emotional/behavioral development, and mothers’ long-term psychopathological symptoms. Method: A total of 113 children (58 boys, 55 girls), originally diagnosed with IA, and their mothers, were evaluated at four assessment points at the children’s mean age of 2, 5, 7, and 11 years. Several measures were used to assess the children’s growth and level of malnutrition, mothers’ psychopathological symptoms and eating attitudes, as well as their children’s emotional/behavioral functioning. Results: A steady improvement in the severity of malnutrition over time emerged, but 73% of children still had ongoing mild to moderate to severe malnutrition at 11 years of age. Moreover, the children showed increasing internalizing and externalizing emotional/behavioral problems, and their mothers’ psychopathological symptoms and eating problems worsened as well over time. At 11 years of age, the girls’ emotional/behavioral problems and their mothers’ psychopathology and disturbed eating attitudes were more severe than that of the boys and their mothers. Finally, during the last assessment, significant associations between the mothers’ psychopathology and disturbed eating attitudes, the severity of the children’s malnutrition and their emotional/behavioral problems emerged. Discussion: Our longitudinal study points out that the developmental course of children, originally diagnosed with IA and who received limited psychosocial treatment, is characterized by an enduring risk of malnutrition and increasing psychopathological symptoms in both, the children and their mothers, up to the sensitive period of pre-puberty.